2022
DOI: 10.1021/acs.jproteome.2c00519
|View full text |Cite
|
Sign up to set email alerts
|

Diversity Matters: Optimal Collision Energies for Tandem Mass Spectrometric Analysis of a Large Set of N-Glycopeptides

Abstract: Identification and characterization of N-glycopeptides from complex samples are usually based on tandem mass spectrometric measurements. Experimental settings, especially the collision energy selection method, fundamentally influence the obtained fragmentation pattern and hence the confidence of the database search results (“score”). Using standards of naturally occurring glycoproteins, we mapped the Byonic and pGlyco search engine scores of almost 200 individual N-glycopeptides as a function of collision ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…One of the influencing factor in some cases is peptide sequence, which was already implied for Byonic score using sce methods. 38 Here, we found the largest impact of sequence for the Byonic score and pGlyco peptide score. For example, the outlier ENGTISR (derived from AGP, ID: P02763 • A1AG1_HUMAN) has well-separated sets of points with different slopes and intercepts.…”
Section: ■ Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…One of the influencing factor in some cases is peptide sequence, which was already implied for Byonic score using sce methods. 38 Here, we found the largest impact of sequence for the Byonic score and pGlyco peptide score. For example, the outlier ENGTISR (derived from AGP, ID: P02763 • A1AG1_HUMAN) has well-separated sets of points with different slopes and intercepts.…”
Section: ■ Introductionmentioning
confidence: 59%
“…34,37,42,43 Regarding the generic workflows, it has been observed that linear optimal CE vs m/z correlation still has large residuals. 38 Some relevant factors have been identified in the literature but always on a limited set of glycopeptides and/or from the view of fragmentation (not from scoring/confident identification). Furthermore, the findings are somewhat contradictory to each other.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most widely used fragmentation technique is CID, where the applied CE has profound impact on the information content of the obtained MS/MS spectra. In particular, this phenomenon has been widely documented from practical proteomics aspects for both unmodified peptides 39,40 and peptides with post‐translational modifications 41–47 . It was shown to be important to use instrument specific optimal setting to achieve best proteomics performance in terms of identification scores and number of successful identifications 40,48,49 …”
Section: Introductionmentioning
confidence: 99%
“…In particular, this phenomenon has been widely documented from practical proteomics aspects for both unmodified peptides 39,40 and peptides with post-translational modifications. [41][42][43][44][45][46][47] It was shown to be important to use instrument specific optimal setting to achieve best proteomics performance in terms of identification scores and number of successful identifications. 40,48,49 The present study focuses on the influence of the application of IMS on the optimum CE at the individual peptide level for a large number of peptides.…”
Section: Introductionmentioning
confidence: 99%